Case definitions for chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME): a systematic review. Issue 2 (7th February 2014) - Brurberg, Kjetil Gundro; Fønhus, Marita Sporstøl; Larun, Lillebeth; Flottorp, Signe; Malterud, Kirsti
Abstract : Objective: To identify case definitions for chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME), and explore how the validity of case definitions can be evaluated in the absence of a reference standard. Design: Systematic review. Setting: International. Participants: A literature search, updated as of November 2013, led to the identification of 20 case definitions and inclusion of 38 validation studies. Primary and secondary outcome measure: Validation studies were assessed for risk of bias and categorised according to three validation models: (1) independent application of several case definitions on the same population, (2) sequential application of different case definitions on patients diagnosed with CFS/ME with one set of diagnostic criteria or (3) comparison of prevalence estimates from different case definitions applied on different populations. Results: A total of 38 studies contributed data of sufficient quality and consistency for evaluation of validity, with CDC-1994/Fukuda as the most frequently applied case definition. No study rigorously assessed the reproducibility or feasibility of case definitions. Validation studies were small with methodological weaknesses and inconsistent results. No empirical data indicated that any case definition specifically identified patients with a neuroimmunological condition. Conclusions: Classification of patients according to severity and symptom patterns, aiming to predict prognosis or effectiveness of therapy, seems useful. Development of further case definitions of CFS/ME should be given a low priority. Consistency in research can be achieved by applying diagnostic criteria that have been subjected to systematic evaluation.